Factors to enhance the development of inclusive university communities: ideas, beliefs and attitudes of university teachers towards disability - Polo Sánchez, M. Tamara; Fernández Cabezas, María; Fernández Jiménez, Carolina (Anales de Psicología / Annals of Psychology, 2021)
The success of the processes of inclusion depends on several factors, including the level of empowerment of the educational community in the process where the role of teachers is a key element, because their attitude and expectations of students with special educational needs will influence their self-esteem, motivation and learning. This article investigates the ideas, beliefs and attitudes towards SEN students demonstrated by teachers, and analyses the variables of gender, age, years of teaching experience, contacts and information about disability on these attitudes. Overall, it was observed that teachers’ attitudes were positive; however they showed a lack of knowledge of the experiences of inclusion of students with disabilities at the university and required more training and information. The results are discussed, the limitations of the study are presented, and suggestions for future research are offered